The Efficacy of Downlisting the African Elephant under CITES: A Critical Assessment - Braby, Justine (Institute of Marine and Environmental Law, 2014)
International trade in wildlife and endangered species is an extremely lucrative business, bringing in an estimated five billion US dollars annually. This makes it one of the world's largest industries. Nearly one third of this trade is illegal. Millions of animals suffer and die each year at the hands of man, often due to human greed and vanity. This international market for animals has led to drastic declines in the populations of many species, including such exotic animals as the rhino, leopard, tiger, and the African elephant. The African elephant's plight has arguably been the most popular. Due to trade in its ivory, African elephant populations declined so dramatically that experts claimed the elephant would be extinct by 2010. This paper examines the steps taken by international law to protect the African elephant, and specifically looks at the two strategies adopted by the African countries to ensure this protection.